Estimation of Carbon Sequestration in Tropical Peat Swamp Forest in Central Kalimantan Using Satellite Based on Primary Productivity - Agustin, Dewa Ayu Mery; Osawa, Takahiro; Ardhana, I Putu Gede (International Journal of Environment and Geosciences; Vol 2 No 2 (2018)DO - 10.24843/ijeg.2018.v02.i02.p01, 2018)
One of approach that can be used to estimate the carbon sequestration by vegetation is to calculate the Gross Primary Productivity (GPP) in Central Kalimantan. GPP is total carbon that can be absorbed by vegetation to be used in the process of photosynthesis. The purpose of this study is to estimate the value of GPP using Vegetation Photosynthesis and Respiration Model (VPRM) and analyze the data comparison between GPP value data derived from flux tower and GPP value data from MODIS data. The field data from flux tower was taken by Hirano et al. (2007) from January 1, 2004 to December 31, 2005. The MODIS data is used MODIS Surface Reflectance Level 3 data year 2004 to 2005. According to the result of this study, the maximum GPP value year 2004 and 2005 showed 302.365 gC m-2 per month (February 2004) and 366.841 gC  m-2 per month (June 2005). The minimum GPP value year 2004 and 2005 was 166.003 gC m-2 per month (November 2004) and 187.663 gC m-2 per month (March 2005). The total value of GPP in year 2004 was 1,134.231 gC m-2 yr-1 and in year 2005 the value was 1,109.001  gC m-2 yr-1. The correlation coefficient between GPP value from flux tower and GPP value from MODIS – VPRM showed in dry season, r = 0.766 and in rainy season, r = 0,839.